Inhibition of CXCR3‐mediated chemotaxis by the human chemokine receptor‐like protein CCX‐CKR. (25th February 2013) - Vinet, J; van, M; Dijkstra, IM; Brouwer, N; van, HRJ; Watts, A; Meijer, M; Fokkens, MR; Kannan, V; Verzijl, D; Vischer, HF; Smit, MJ; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Induction of cellular migration is the primary effect of chemokine receptor activation. However, several chemokine receptor‐like proteins bind chemokines without subsequent induction of intracellular signalling and chemotaxis. It has been suggested that they act as chemokine scavengers, which may control local chemokine levels and contribute to the function of chemokines during inflammation. This has been verified for the chemokine‐like receptor proteins D6 and DARC as well as CCX‐CKR. Here, we provide evidence for an additional biological function of human (h)CCX‐CKR. Experimental Approach We used transfection strategies in HEK293 and human T cells. Key Results Co‐expression of hCCX‐CKR completely inhibits hCXCR3‐induced chemotaxis. We found that hCCX‐CKR forms complexes with hCXCR3, suggesting a relationship between CCX‐CKR heteromerization and inhibition of chemotaxis. Moreover, negative binding cooperativity induced by ligands both for hCXCR3 and hCCX‐CKR was observed in cells expressing both receptors. This negative cooperativity may also explain the hCCX‐CKR‐induced inhibition of chemotaxis. Conclusions and Implications These findings suggest that hCCX‐CKR prevents hCXCR3‐induced chemotaxis by heteromerization thus representing a novel mechanism of regulation of immune cell migration.